Radiation induced soft errors in 16 nm floating gate SLC NAND flash memory. (May 2020) - Chandrashekhar, Sandhya; Puchner, Helmut; Mitani, Jun; Shinozaki, Satoshi; Sardi, Mohamed; Hoffman, David
Abstract: 16nm single-level-cell (SLC) NAND flash memories with 1-bit ECC are shown to have excellent robustness to soft errors induced by terrestrial neutron radiation and alpha particles. Accelerated stress test studies were done at TRIUMF Neutron Facility for neutron induced soft errors and using calibrated alpha sources for accelerated alpha particle testing. Our results demonstrate excellent robustness of the memory device to soft error latch-up and single event upsets. Additionally, we report cross-site correlation results of accelerated alpha particle testing of 16nm NAND flash memories by comparing test results using Am-241 and Th-232 foils for higher confidence in the failure rate calculations. An acceleration factor of 1.66 × 10 4 between the two foils was used.